Fuzziness-vagueness-generality-ambiguity - Zhang, Grace (Elsevier, 1998)
In this paper, I attempt to distinguish four linguistic concepts: fuzziness, vagueness, generality and ambiguity. The distinction between the four concepts is a significant matter, both theoretically and practically. Several tests are discussed from the perspectives of semantics, syntax and pragmatics. It is my contention that fuzziness, vagueness, and generality are licensed by Grice's Co-operative Principle, i.e. they are just as important as precision in language. It is concluded that generality, vagueness, and fuzziness are under-determined, and ambiguity is over-determined. Fuzziness differs from generality, vagueness, and ambiguity in that it is not simply a result of a one-to-many relationship between a general meaning and its specifications; nor a list of possible related interpretations derived from a vague expression; nor a list of unrelated meanings denoted by an ambiguous expression. Fuzziness is inherent in the sense that it has no clear-cut referential boundary, and is not resolvable with resort to context, as opposed to generality, vagueness, and ambiguity, which may be contextually eliminated. It is also concluded that fuzziness is closely involved with language users' judgments. An important implication of this is that for meaning investigations, an integral approach combining semantics, pragmatics, and psycholinguistics would be more powerful and beneficial.